Iron oxide nanoparticles inside the MCM-41 channels: Study of the structural stability of the support - Bengoa, Jose Fernando (2005)
We report the synthesis of the MCM-41 mesoporous solid chosen as support of Fe nanoparticles, which yields a narrow distribution of oxide crystal sizes. MCM-41 was synthesized in two different ways, with and without pH adjustment during the synthesis process, and impregnated by different methods with iron salts. They were characterized by atomic absorption spectroscopy, N2 adsorption, X-ray diffraction, Mössbauer spectroscopy, high-resolution scanning transmission electron microscopy equipped with a high-angle annular dark-field detector, high-resolution transmission electron microscopy and energy dispersive X-ray spectroscopy. When the support was synthesized without pH adjustment the preparation steps of the supported system, the water destroys the regular structure of hexagonal channels of the mesoporous solid. The structure is preserved when the support is synthesized with pH adjustment during the synthesis process due to its higher pore-wall thickness. In addition, this system has a higher percentage of the iron oxide nanocrystals located inside the channels of the support. © 2005 Elsevier Inc. All rights reserved.